Implementasi Kegiatan Pramuka dalam Membentuk Karakter Disiplin Siswa Kelas V SD Inpres Boru Kecamatan Wulanggitang Kabupaten Flores Timur - Hermus Hero (Jurnal Ilmiah Wahana Pendidikan, 2021)
The purpose to be achieved in this research is to describe how the implementation of scouting activities in shaping the disciplinary character of the fifth grade students of SD Inpres Boru, Wulanggitang District, East Flores Regency. This study was to determine the implementation of scouting activities in shaping the character of students at SD Inpres Boru. In an effort to obtain the truth or seek answers to existing problems, the researchers used a qualitative approach. The efforts of the coach in instilling disciplinary character values ​​through scouting activities are carried out with habituation, exemplary examples, giving assignments, giving lectures or advice, and giving sanctions if students make mistakes.